The impact of landscape setting towards the surrounding microclimate: a case study of IIUM courtyards - Mohed, Abdul Hadi; Zakaria, Mohamad Faruq; Abu Bakar, Aniza (2015)
Malaysia is experiencing rapid changes particularly in its urban setting. While the changes is important, it is also brings negative impacts. Following the urbanization, more natural surfaces are transformed into man-made structures. It is observed that the urban temperature is increasing. Hence, the urban heat island (UHI) phenomenon is observed. This research is an attempt to investigate the influence of landscape setting on the microclimate with focus on the vegetation and ground surface material towards the UHI mitigation. To achieve the aim of the research, four courtyard within the academic building at the International Islamic University Malaysia (IIUM) were selected as the case study sites. The physical dimension of the courtyards which include the height to width ratio (H/W), orientation, opening, as well as types of vegetation and ground surface material was investigated. Shadow analysis was also conducted by using the Sketchup™ software. The environmental parameter such as air temperature (˚C), surface temperature (˚C), solar radiation (W/m2), wind speed (m/s), relative humidity (%) and sky condition (oktas). It is hoped that the influence of the landscape setting on the microclimate can be further understood and design recommendations are provided.